What Can Low-Income Countries Expect From Adopting Inflation Targeting? - Born, Alexandra (IMF Working Papers; Working Paper, 2011)
Inflation targeting (IT) is a relatively new monetary policy framework for low-income countries (LICs). The limited number of LICs with an IT framework and the short time that has elapsed since the adoption of this framework explains why there are no previous empirical studies on the performance of IT in LICs. This paper has made a first attempt at filling this gap. It finds that inflation targeting appears to be associated with lower inflation and inflation volatility. At the same time, there is no robust evidence of an adverse impact on output. This may explain the appeal of IT for many LICs, where building credibility of monetary policy is difficult and minimizing output costs of reducing inflation is imperative for social and political reasons.